M. S. Bazykin as a critic and book art theorist - D. V. Fomin (Библиосфера, 2018)
The scientific heritage of M. S. Bazykin is small, but still of considerable interest for book art researchers. In particular, he contributed much to study, description and promotion of a book sign as a phenomenon. His works on the book plates are written with a clear understanding of very special problems of this type of graphics. The scholar considers bookplate as a sort of an allegorical portrait of the owner giving an idea of his personality, profession, circle of interests, aesthetic preferences, composition and nature of his library. A bookplate should have succinct and laconic expressiveness, as well as ought to fit easily into the book artistic structure. In accordance with these requirements the art critic evaluated works by I. N. Pavlov, A. I. Kravchenko, M. V. Matorin, N. V. Puzyrevskiy, and other artists, demonstrating a broad spectrum of aesthetic views, delving into the essence of a creative method of each author. In his reviews touching the book graphics, M. S. Bazykin paid a special attention to details of their design, demonstrating his evident preference of strict and severe designer solutions. He was annoyed by ostentatious luxury of certain editions motivated by neither their content, nor readers′ target audience. At the same time he was interested and almost always favourable towards art editions realized in the provinces. Important and significant judgments, concerning prominent publishers and printers, designers and polygraphists of those years should be found in his still unpublished texts stored in the Russian state archive of Literature and Art (RGALI). For instance, in his reports Bazykin analyzes causes of disastrous situation with newly released art books, considering except for design merits and shortcoming various other factors of economical, sociological and management characters. In his papers the scientist poses a fundamentally important question: who of contemporary book designers can be considered as a real book artist, equally competent in both technical and aesthetic aspects. Strictly speaking, besides rare exceptions, such universal «artists-designers» didn′t exist for that moment, but it were them, whom Bazykin pinned his hopes on radical renewal of image of Russian book with. Undoubtedly, should his talent develop under favorable conditions, he might have easily become one of the most respected and competent scholars of book art. However, he managed to do quite a lot even in the short time period allotted to him.